RELIGIOUS PSYCHOLOGY OF CHILDREN AND YOUTH IN RELATION TO RELIGIOUS COUNSELING PROGRAMS AND STRATEGIES - Yuliana Nelisma; Muslima Muslima; Elviana Elviana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The study in this research is about the religious psychology of children and adolescents in relation to religious counseling programs and strategies. The research model used is a literature study that discusses the religious psychology of children and adolescents in relation to religious counseling programs and strategies, referring to articles or findings related to this matter.